Development of a microcontroller-based inverter for photovoltaic application - Sharulnizam, Mohd Mukhtar (Universiti Malaysia Perlis (UniMAP), 2012)
Presented in this thesis is the development of a microcontroller-based inverter for photovoltaic systems. A single 8-bit microcontroller generated switching pulses for both stages of the inverter’s dc-dc converter and dc-ac inverter. A simple, effective algorithm suitable for implementation in a single 8051 microcontroller was developed, for control of the inverter’s power stage. The thesis explained details on the PWM and the SPWM switching strategies including calculation to presents their switching pulse widths. An inverter of 500W capacity was built to test the switching pulse generated by the microcontroller. A high frequency (HF) planar transformer raised input voltage to the inverter’s required level and provided isolation and solving difficulties in producing a handmade conventional HF transformer. The experiment were conducted in laboratory environment, where input voltage was taken from DC power supply and the inverter load was purely resistive. The prototype’s performance analysis results were found to be similar to those calculated. The prototype inverter performed well that able to produce a stable 240V output voltage at 50Hz, able to handle loads up to 500W, and had a low THD.